Performance and differential costs analysis in a two echelons repair system with infinite servers queues - Ferreira, M. A. M.; Filipe, J. A.; Coelho, M. (Advanced Materials Research, 2014)
Using infinite servers queues systems parameters, focused on its busy period, the performance and the differential costs of a two echelons repair system are analyzed through a model constructed with this goal. This kind of repair systems may be useful, for instance, in the operation of a fleet either of aircraft, or of shipping or of trucks.